INTRA-AORTIC BALLOON PUMP IN CORONARY ARTERY BYPASS GRAFT - FACTORS AFFECTING OUTCOME - Okonta, KE (West African College of Surgeons, 2011)
BACKGROUND: The management of coronary artery bypass graft (CABG) patients, especially in high risk patients ,can be challenging as the postoperative periods may be characterized by a low cardiac output state. Inotropes used in the perioperative periods to increase cardiac output may be detrimental thus making the use of mechanical devices like intra-aortic Balloon pump (IABP) for circulatory assistance desirable. AIMS & OBJECTIVES: To study the use of intra-aortic balloon pump in coronary artery bypass patients in preoperative and post operative settings and factors that affect morbidity and mortality. SETTING: Madras Medical Mission, Chennai, India. METHOD: A retrospective study of 3974 consecutive patients who had CABG done between March 2007 and February 2011 with or without additional procedures. One hundred and seven (2.7%) patients had IABP instituted either pre-operatively or postoperatively when it was obvious the patient will need cardiac assistance. The demographic data, clinical features, the indications for insertion, management offered and outcome , the creatinine levels, the duration of intraarortic balloon pump, the intensive care unit(ICU) and Hospital stay were analyzed for means and standard deviations and Pearsons Chi-square test using SPSS 10.0 window soft ware version with significant value of p-value<0.005. RESULT: The mean age of all the patients was 59.7 + SD 10.7, 85(79.4%) patients were males,22(20.6%) were females .Out of the 107 patient who had IABP insertion, 59(55.1%) patients had IABP inserted preoperatively and 48(44.9%) postoperatively. The creatinine levels after the insertion of IABP in 68 patients was<1.5mg/dl and in 39 patients was>1.5mg/dl with mortality of 15.0% for the preoperative insertion group versus 29.0% for the postoperative group respectively (p=0.005). The preoperative and postoperative insertion ICU stay were 8.3+4.7 days and 5.7+1.6days respectively (p=0.005) and mortality were16.8% and 27.1 %( p=0.005) respectively CONCLUSION: Early institution of intra-aortic balloon pump gives a better outcome even in high risk coronary artery bypass graft patients as it reduces ICU stay and mortality, and elevated post-insertion creatinine levels has been shown to be an indicator of impending mortality and so an early warning for putting in place mitigating protocols.